Analisis Risiko Kerja pada Area Hot Metal Treatment Plant Divisi Blast Furnace dengan Metode Hazard Identification and Risk Assessment (HIRA) - Anthony, Muhamad Bob (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2019)
This study aims to determine the value of the risk of work hazard potential and the level of risk of potential occupational hazards in the blast furnace division of hot metal treatment plant which is currently in the commissioning stage. This study uses an approach with the HIRA (Hazard Identification and Risk Assessment) method to determine the value of the risk of potential occupational hazards and the level of risk of potential occupational hazards. The results obtained by using HIRA (Hazard Identification and Risk Assessment) obtained 26 risks classified by potential hazards, namely nine risks included in the high category (H), seven risks moderate category (M) and the remaining ten risks involved in the low category ( L). The recommendation that can give is to carry out detailed mitigation of the risk of high (H) and moderate (M) categories until the risk level falls to the risk of the low (L) category before the blast furnace plant is fully operating.